A Narrative Orientated Inquiry Exploring the Key Stage 2-3 Transition Experiences of Young People with SEMH Needs in Mainstream Schools - McCrossan, Gary (2023)
Key Stage 2-3 (KS2-3) transition is experienced by the majority of young people attending mainstream schools in England. Research suggests that, whilst most young people are able to navigate this transition successfully, for some it may represent a period of significant social, emotional, and academic challenge (Jindal-Snape et al., 2020). Furthermore, difficulties during transition may be associated with negative social, emotional, and academic outcomes (Hopwood & Dyment, 2016; West et al., 2010; Zeedyk et al., 2003). Research suggests that in comparison to their peers, young people with Social Emotional, and Mental Health (SEMH) needs may be more likely to encounter experiences associated with a difficult KS2-3 transition experience (Cefai & Cooper, 2010; Cosma & Soni, 2019).